Conceptualisation of event roles in L1 and L2 by Japanese learners of English: a cross-linguistic comparison of perspectives of event construal - Qu Jiashen; Miwa Koji (Cognitive Linguistics)
Events can be perceived from different perspectives. Langacker, Ronald W. (1990. Subjectification. Cognitive Linguistics 1. 5–38) typologically categorised the perspectives in event construal as subjective construal and objective construal based on how egocentric a perspective is. Compared with Western languages, such as English, Japanese is argued to be a language that favours subjective construal. However, little empirical work has tested this assumption directly. We investigated whether Japanese and English construe events from different perspectives by focusing on the linguistic encodings of event roles “agent” and “patient”. Our findings show that when selecting event roles as sentence subjects, Japanese speakers prioritised animacy over agency whereas English speakers emphasised agency (while also considering animacy). This can be attributed to the different preferences of the two languages for the degree of egocentricity in event construal. Furthermore, we explored how L1-based conceptualisation of event roles influences the linguistic expressions of event roles in L2. Our results demonstrate that Japanese learners of English had difficulty reconceptualising event roles in L2 English. This study adds a piece of quantitative evidence to the cognitive linguistics theory on subjective construal in Japanese and questions the universality of the agent-first hypothesis in the Thematic Hierarchy.